Effect of Global Ventilation to Perfusion Ratio, for Normal Lungs, on Desflurane and Sevoflurane Elimination Kinetics. (9th November 2021) - Baumgardner, James E.; Kretzschmar, Moritz; Kozian, Alf; Hachenberg, Thomas; Schilling, Thomas; Larsson, Anders; Hedenstierna, Göran
Abstract : Background: Kinetics of the uptake of inhaled anesthetics have been well studied, but the kinetics of elimination might be of more practical importance. The objective of the authors' study was to assess the effect of the overall ventilation/perfusion ratio (VA /Q), for normal lungs, on elimination kinetics of desflurane and sevoflurane. Methods: The authors developed a mathematical model of inhaled anesthetic elimination that explicitly relates the terminal washout time constant to the global lung VA /Q ratio. Assumptions and results of the model were tested with experimental data from a recent study, where desflurane and sevoflurane elimination were observed for three different VA /Q conditions: normal, low, and high. Results: The mathematical model predicts that the global VA /Q ratio, for normal lungs, modifies the time constant for tissue anesthetic washout throughout the entire elimination. For all three VA /Q conditions, the ratio of arterial to mixed venous anesthetic partial pressure Part /Pmv reached a constant value after 5 min of elimination, as predicted by the retention equation. The time constant corrected for incomplete lung clearance was a better predictor of late-stage kinetics than the intrinsic tissue time constant. Conclusions: In addition to the well-known role of the lungs in the early phases of inhaled anesthetic washout, the lungs play a long-overlooked role in modulating the kinetics of tissue washout during the later stages of inhaled anesthetic elimination. The VA /Q ratio influences the kinetics of desflurane and sevoflurane elimination throughout the entire elimination, with more pronounced slowing of tissue washout at lower VA /Q ratios. Abstract : A mathematical model of inhaled anesthetic elimination was developed in a post hoc analysis of anesthetic partial pressures measured in mixed venous and arterial blood samples after simultaneous administration of desflurane and sevoflurane to seven piglets under normal, low, and high ventilation/perfusion ratio conditions. After a brief and rapid decline in alveolar anesthetic partial pressure, the fractional clearance of anesthetic became constant, and incomplete clearance from the lungs slowed tissue washout. Slowing of tissue elimination by incomplete lung clearance became more pronounced at low ventilation/perfusion ratios, and was predicted to become more pronounced as blood/gas solubility increases.